Travelling Wave solutions of hyperbolic Telegraph equation by Tanh method (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Tanh method is utilized to find travelling solutions of second order nonlinear Telegraph equation. As a result, we attain dissimilar travelling wave solutions. Our aim is to show that this method is most efficient and convenient approach for verdict travelling wave solutions of nonlinear differential equations. For calculation the software MAPLE is used.